Vascular Calcification: New Insights Into BMP Type I Receptor A - Niu, Zhixing; Su, Guanyue; Li, Tiantian; Yu, Hongchi; Shen, Yang; Zhang, Demao; Liu, Xiaoheng (Frontiers in Pharmacology, 2022)
Vascular calcification (VC) is a complex ectopic calcification process and an important indicator of increased risk for diabetes, atherosclerosis, chronic kidney disease, and other diseases. Therefore, clarifying the pathogenesis of VC is of great clinical significance. Numerous studies have shown that the onset and progression of VC are similar to bone formation. Members of the bone morphogenetic protein (BMP) family of proteins are considered key molecules in the progression of vascular calcification. BMP type I receptor A (BMPR1A) is a key receptor of BMP factors acting on the cell membrane, is widely expressed in various tissues and cells, and is an important “portal” for BMP to enter cells and exert their biological effect. In recent years, many discoveries have been made regarding the occurrence and treatment of ectopic ossification-related diseases involving BMP signaling targets. Studies have confirmed that BMPR1A is involved in osteogenic differentiation and that its high expression in vascular endothelial cells and smooth muscle cells can lead to vascular calcification. This article reviews the role of BMPR1A in vascular calcification and the possible underlying molecular mechanisms to provide clues for the clinical treatment of such diseases.